2015
DOI: 10.1590/1519-6984.05614
|View full text |Cite
|
Sign up to set email alerts
|

Edge effects on the blowfly fauna (Diptera, Calliphoridae) of the Tijuca National Park, Rio de Janeiro, Brazil

Abstract: In this contribution we examine the diversity, abundance and species richness of Calliphoridae in the Tijuca National Park, Rio de Janeiro, RJ. Specimens were collected monthly between September 2009 and August 2010, using sardines as bait, in three points: A, on the forest edge (22°56'846"S 43°17'496"W), B, 700m from it (22°57'073"S 43°17'832"W) and C, 1,200m into the forest (22°57'321"S 43°18'031"W), evaluating the indicator species at each point and the anthropogenic influences and abiotic factors that dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
(33 reference statements)
2
3
0
Order By: Relevance
“…In the first case it differs from that found by [ 20 ], while in the second case it corroborates with this author. The genus Chrysomya was the most synanthrope in this study, agreeing with [ 21 ]. However, for C .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the first case it differs from that found by [ 20 ], while in the second case it corroborates with this author. The genus Chrysomya was the most synanthrope in this study, agreeing with [ 21 ]. However, for C .…”
Section: Discussionsupporting
confidence: 92%
“…Diptera sampling studies are of fundamental importance to analyze ecological behavior, such as population dynamics, diversity, distribution, dispersal areas and seasonality of exotic and native species. As mesembrinelids represent an asynanthrope and bioindicator group [9] and Calliphorids have high adaptability to anthropomorphized environment, with high specimen dispersion and numerous offspring, thus possessing synanthropic species [10], more work on the synanthropy of these two families is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Chrysomya was collected in urban and rural environments, with C. megacephala as constant and intermediate in both environments and accessory and intermediate in general. C. albiceps was considered accessory and rare in the urban environment, accessory and intermediate in the rural environment, and accidental and intermediate in general, which corroborates the findings of [ 39 ], who showed this species preferring anthropic areas. Other studies have shown the presence of this species included in environments close to forest areas in the state of Rio de Janeiro, such as [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 88%
“…L. eximia was the predominant species in different collection environments in [ 37 ]; similarly, this study presented it as constant and common in the three environments. However, for L. cuprina , several studies in the Atlantic Forest, such as [ 36 , 38 , 39 ], show this species presenting low frequency or being absent; in this work, the species was constant and intermediate in the rural environment and accessory and constant in all three locations.…”
Section: Discussionmentioning
confidence: 47%
“…Additional information obtained from screwworm adult captures contributed to providing a more complete distribution of C. hominivorax in the country ( Figure 2D, Table 2). Adults of C. hominivorax have been caught in several sites, mainly by traps baited with carcasses (ALVES et al, 2014;FARIA et al, 2018), rotting viscera or other decaying material (KOLLER et al, 2002(KOLLER et al, , 2011SOUSA et al, 2010;GONÇALVES et al, 2011;GADELHA et al, 2015;PEREIRA DE SOUSA et al, 2015OLIVEIRA et al, 2016). Although decaying baits are not the best attractant to a fly species causing primary myiasis, this relatively inexpensive and simple choice has provided useful information on the distribution of C. hominivorax in Brazil (Figure 2E).…”
Section: Adult Recordsmentioning
confidence: 99%